Interpretation of the Quranic Verses and Indonesian Marriage Law on Interfaith Marriage - Munir, Akmal Abdul; Zikri, Ahmad; Farhan, Ahmad; Ahmad, Afrizal; Supriadi, Supriadi (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2024)
One of the social phenomena that occurs among Muslims today is interfaith marriage, which raises various pros and cons. This fact and discourse is still being discussed, especially with the application to the Constitutional Court (MK) to conduct a judicial review of the marriage law. However, the Constitutional Court rejected the application, and various parties were not satisfied with this decision because whether an interfaith marriage is valid is the domain of each religion. Normatively, the narrative of interfaith marriage has been mentioned in the Quran in Surah al-Baqarah verse 221. In the case of Rizky Febian's marriage to Mahalini, who was originally Hindu and has become a muallaf. The theological basis is still strong as a consideration for a Muslim when deciding to get married. This study will explore the interpretation of Quranic verses related to interfaith marriage from various mufassirs, which are also related to the Indonesian marriage law. As a literary research, the data used are the Quran, books of commentaries, laws on marriage, and articles relevant to this research. The results show that the scholars' interpretation suggests that interfaith marriage is forbidden. Even in the perspective of the state, interfaith marriage is still prohibited. Even so, some opinions allow believing men to marry women of the People of the Book but forbid women of other religions. Pernikahan beda agama merupakan fenomena sosial yang banyak terjadi di kalangan umat Islam saat ini, dan mempunyai kelebihan dan kekurangan. Fakta dan wacana tersebut masih menjadi perdebatan, khususnya dengan adanya permohonan uji materiil undang-undang perkawinan ke Mahkamah Konstitusi (MK). Namun Mahkamah Konstitusi menolak kasus tersebut dan banyak pihak yang tidak puas dengan putusan tersebut karena masing-masing agama menentukan boleh atau tidaknya pernikahan beda agama. Biasanya Al-Quran menyebutkan pernikahan beda agama dalam surat al-Baqarah ayat 221. Dalam kasus pernikahan Rizki Febrian dengan Mahallini yang awalnya beragama Hindu dan kemudian menjadi muallaf, jelas bahwa pertimbangan teologis tetap penting bagi umat Islam dalam memilih untuk menikah. Kajian ini akan melihat bagaimana berbagai mufassir memahami teks-teks Alquran tentang pernikahan beda agama, yang juga relevan dengan hukum pernikahan di Indonesia. Sebagai penelitian kepustakaan, data yang digunakan adalah Alquran, tafsir, hukum perkawinan, dan artikel yang relevan dengan pembahasan. Temuan ini menunjukkan bahwa penafsiran para ulama menyatakan bahwa pernikahan beda agama dilarang. Dalam pandangan negara, pernikahan beda agama masih dilarang. Meskipun demikian, sebagian orang berpendapat bahwa laki-laki boleh menikahi wanita yang Ahli Kitab tetapi tidak boleh menikahi wanita yang beragama lain.